Influence of size and insertion depth of irrigation needle on debris extrusion and sealer penetration - Emel Uzunoglu-Özyürek; Hakan Karaaslan; Sevinç Aktemur Türker; Bahar Özçelik (Restorative Dentistry & Endodontics)
ObjectivesTo determine the effect of size and insertion depth of irrigation needle on the amount of apical extruded debris and the amount of penetration depth of sealer using a confocal laser scanning microscope (CLSM).Materials and MethodsTwenty maxillary premolars were assigned to 2 groups (n = 10), according to the size of needle tip, 28 G or 30 G. Buccal roots of samples were irrigated with respective needle type inserted 1 mm short of the working length (WL), while palatal roots were irrigated with respective needle type inserted 3 mm short of the WL. Prepared teeth were removed from the pre-weighed Eppendorf tubes. Canals were filled with F3 gutta-percha cone and rhodamine B dye-labeled AH 26 sealer. Teeth were transversally sectioned at 1 and 3 mm levels from the apex and observed under a CLSM. Eppendorf tubes were incubated to evaporate the irrigant and were weighed again. The difference between pre- and post-weights was calculated, and statistical evaluation was performed.ResultsInserting needles closer to the apex and using needles with wider diameters were associated with significantly more debris extrusion (p < 0.05). The position of needles and level of sections had statistically significant effects on sealer penetration depth (p < 0.05 for both).ConclusionsFollowing preparation, inserting narrower needles compatible with the final apical diameter of the prepared root canal at 3 mm short of WL during final irrigation might prevent debris extrusion and improve sealer penetration in the apical third.